POTENSI EKSTRAK RUMPUT LAUT COKLAT (Sargassumprismaticum) UNTUK MENINGKATKAN AKTIVITAS SUPEROKSIDA DISMUTASE (SOD) DAN GAMBARAN HISTOLOGI JARINGAN HEPAR PADA TIKUS (Rattus norvegicus) DIABETES MELITUS TIPE 1 - Sari, Ardian Retno; Prasetyawan, Sasangka; Aulanni’am, Aulanni’am (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
The aim of this research was to investigate the ability of brown seaweed (Sargassum prismaticum) extract that can increase the activity of SOD and improvement of hepar tissue on rats Rattus norvegicus type 1 diabetes mellitus the results of multiple low dose-streptozotocin (MLD-STZ) induction with 20 mg/kg (bw) dose for 5 consecutive days. As many as 24 rats were devided into 6 groups of 4 each tail. Group treatments were the group of control, type 1 diabetes mellitus, and type 1 diabetes mellitus that given by therapy of Sargassum prismaticum extract orally with variations of given therapy on the different  days to 1, 3, 5, and 7. SOD activity were measured by Elisa Reader Kit on the wavelength at 450 nm and histology description with hematoxylin-eosin staining. The results of this research obtained that SOD activity after given by Sargassum prismaticum extract have been raised and the results as follow as 53,80 (unit/mL), 63,78 (unit/mL), 73,67 (unit/mL), 83,85 (unit/mL). Sargassum prismaticum therapy can fixed the damage of DM type 1 hepar tissue on rats that have been induction by MLD-STZ. Keyword : Diabetes Mellitus, Hepar, Histology, SOD